ANALYSIS OF ACTING ON THE TERRITORY OF THE ROSTOV REGION OF THE SYSTEM OF TARGETED PROGRAMME PLANNING OF WATER MANAGEMENT - Ekaterina Aidarkina (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the main programs in the area of water management, implemented on the territory of the Rostov region. Analyzed the main activities planned within the framework of these programmes, rationalization ofwater use and protection and restoration of water bodies in the region. Also the analysis of the structure and funding of these programs.